Analisis Partisipasi Masyarakat Dalam Pembangunan Desa di Desa Bontokape Kecamatan Bolo Kabupaten Bima - Mutmainnah, Lina; Basalamah, Muhammad Ridwan; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine the influence of community participation in the field of planning, the field of organizing, the field of implementation and the field of supervision in improving village development in Bontokape Village, Bolo District, Bima Regency. This research method uses quantitative methods. The population in this study is people living in Bontokape Village since 2019 and village officials who have served since 2019. Determination of the number of samples using the slovin formula and obtained 55 respondents with purposive sampling techniques. The data collection method uses observation, documentation and questionnaires/questionnaires given offline to respondents. The data analysis methods used in this study are research instrument tests (Validity test, Reliability test), Normality Test, Classical assumption test (Multicollinearity test, Heterokedasticity test), Multiple linear analysis, Hypothesis test (t test, f test) and Determination coefficient test using SPSS data processor. The results of the study partially obtained results where community participation in the field of planning did not have a significant effect on village development, community participation in the field of organizing did not have a significant effect on village development, community participation in the field of implementation did not have a significant effect on village development, community participation in the field of supervision did not have a significant effect on village development, due to the large population It is studied to have a social phenomenon of development, the majority of which are still in operational form or in the operational managerial group where elements of planning, organizing, implementing and supervising have been completed in the government and village officials while the village community is more involved or physically participating when activities are carried out. Simultaneously, community participation in the fields of planning, organizing, implementing and supervising has a significant effect on village development. Keywords: Field Of Planning, Organizing, Implementing, Supervising And Developing Villages